Morphological and mechanical analysis of filler based polymer composites and additively manufactured lattices using micro-CT scanning - Jain, Palash Abhineet (Nanyang Technological University, 2021)
Micro-CT scanning as a non-destructive characterization technique has been gaining traction in the study of composite materials and additively manufactured structures, where samples are often costly to manufacture in bulk for any form of testing. This study looks at the utility of micro-CT scanning in the analysis of polycarbonate and polycarbonate-carbon fibre based composites with metal and ceramic fillers as well as an yttria stabilized zirconia simple cubic lattice manufactured from an experimental form of stereolithography. Several techniques for analysing the morphological and mechanical properties of these materials using data from micro-CT scans are presented, alongside their challenges, limitations and areas of improvement. It is concluded that micro-CT scanning for such analysis holds great potential, but is still at its nascent stages owing to a lack of international standards to ensure repeatability of accuracy across experiments.